2019
DOI: 10.1016/j.jid.2018.09.035
|View full text |Cite
|
Sign up to set email alerts
|

TWEAK/Fn14 Interaction Confers Aggressive Properties to Cutaneous Squamous Cell Carcinoma

Abstract: Recent studies showed that TWEAK/Fn14 signaling participates in the progression of internal malignancies. However, its role in the biological properties of cutaneous squamous cell carcinoma (SCC) remains unclear. This study was designed to explore the effect of TWEAK/Fn14 activation on cutaneous SCC as well as the relevant mechanism. The expression of TWEAK and Fn14 was determined in tissue samples of patients with cutaneous SCC. Human primary keratinocytes and SCC cell lines were cultured in vitro, receiving … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 35 publications
(67 reference statements)
2
17
0
Order By: Relevance
“…Moreover, TNFR2 is expressed in some tumor cells and directly promotes proliferation of cells (22). Both Fn14 and TNFR2 are highly expressed in several SCC cell lines, and inhibition of Fn14 or TNFR2 suppresses the growth of SCC xenografts in nude mice (7). Consistently, we found in this study that TNFR2 is highly expressed in SCC-13 cells.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Moreover, TNFR2 is expressed in some tumor cells and directly promotes proliferation of cells (22). Both Fn14 and TNFR2 are highly expressed in several SCC cell lines, and inhibition of Fn14 or TNFR2 suppresses the growth of SCC xenografts in nude mice (7). Consistently, we found in this study that TNFR2 is highly expressed in SCC-13 cells.…”
Section: Discussionsupporting
confidence: 86%
“…Previously, we demonstrated that TWEAK induces proliferation of A431 and SCC-9 cells (SCC cell lines) (7). In this study, SCC-13 cells were utilized to investigate the effect of TWEAK on cell proliferation or apoptosis.…”
Section: Tweak Induces Cytoplasmic Ciap1 Importation and Rip1 Ubiquitmentioning
confidence: 99%
See 1 more Smart Citation
“…Protein lysates were prepared from fresh tissue or cell cultures . Samples were separated on electrophoresis gels, and then transferred onto polyvinylidene difluoride membrane (Millipore, Billerica, MA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…A paracrine mechanism underlying the oxidative stress-induced cutaneous inflammation in vitiligo. Cui et al, 2019;Jian et al, 2014;Li et al, 2017;Quan et al, 2010 (continued ) J Uitto et al Ge et al, 2016;Guo et al, 2016Guo et al, ,2011Hu et al, 2019Lin et al, 2018 Autoimmune bullous diseases…”
Section: Call For International Collaborationsmentioning
confidence: 99%